Dabigatran and warfarin in nonvalvular atrial fibrillation or atrial flutter in outpatient clinic practice in Brazil - Monteiro, Jean Michell Correia; San-Martin, Daniel Lordelo; Silva, Beatriz Carneiro Gondim; Souza, Ian Felipe Barbosa; Oliveira, Jamary, Filho; Jesus, Pedro (Arquivos de Neuro-Psiquiatria, 2019)
Objectives: To compare warfarin and dabigatran for thromboembolic event prevention in patients with nonvalvular atrial fibrillation or atrial flutter.Methods: This was a retrospective cohort of participants with nonvalvular atrial fibrillation or atrial flutter using either warfarin or dabigatran in a reference center in Brazil.Results: There were 112 patients (mean age 65.5 years), with 55.3% using warfarin. The median duration of follow-up was 1.9 years for warfarin and 1.6 years for dabigatran (p = 0.167). Warfarin patients had a higher median of medical appointments per year (8.3 [6.8-10.4] vs 3.1 [2.3-4.2], p < 0.001) and the frequency of minor bleeding was more than four times higher (17.7% vs 4.0%, p = 0.035). Among patients with prior stroke, those using warfarin had 2.6 times more medical appointments for person-years of follow-up (8.5 vs 3.3). There was no major bleeding or embolic event during follow-up period.Conclusion: The dabigatran group had a lower frequency of minor bleeding and number of medical appointments than the warfarin group, without more embolic events or major bleeding.
Keywords: Dabigatran; warfarin; atrial fibrillation; atrial flutter; stroke